2021
DOI: 10.1017/s0007114521002543
|View full text |Cite
|
Sign up to set email alerts
|

The association between lunch composition and obesity in Iranian adults

Abstract: We aimed to assess the dietary composition of lunch meal using a posteriori derived dietary patterns and to determine the association of lunch composition with obesity in a sample of Iranian adults. This cross-sectional study was conducted on 850 men and women in Tehran (aged 20-59 y). Dietary intakes were assessed using three 24-h dietary recalls, and dietary patterns were identified via principal component factor analysis. For each identified pattern, scores were calculated for each participant and then clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Participants at the top tertile of the lunch-specific ‘Bread, grains, and fat’ intake had a higher waist-to-hip ratio compared with those in the lowest tertile. There was not any other significant association (21) . Another cross-sectional study on a total of 840 Iranian adults with an age range of 20–65 years showed a significant association between a lunch-specific animal-based low-carbohydrate diet, collected via 24-h dietary recall, and general obesity after essential adjustments (22) .…”
Section: Discussionmentioning
confidence: 76%
“…Participants at the top tertile of the lunch-specific ‘Bread, grains, and fat’ intake had a higher waist-to-hip ratio compared with those in the lowest tertile. There was not any other significant association (21) . Another cross-sectional study on a total of 840 Iranian adults with an age range of 20–65 years showed a significant association between a lunch-specific animal-based low-carbohydrate diet, collected via 24-h dietary recall, and general obesity after essential adjustments (22) .…”
Section: Discussionmentioning
confidence: 76%
“…Some studies showed that these factors could affect nutritional status. For example, Akbarzade et al discovered that the volume and composition of the midday meal could impact obesity 36 . Therefore, having lunch at the wrong time will be a predisposing factor for obesity and overweight.…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies focusing on meal-specific dietary patterns is growing. We previously reported the association of major dietary patterns at breakfast (64) and lunch (65) and dinner (50) levels with obesity.…”
Section: Discussionmentioning
confidence: 99%